KARAKTERISASI DAN UJI BIOAKTIVITAS SENYAWA KIMIA ANTI TUBERCULOSIS (TBC) PADA SPONS PETROSIA ALFIANI DARI PERAIRAN SELAT MAKASSAR - Rahman, Abd.; Aminah, Ibtisamatul; Muhakim, Ali (Program Kreativitas Mahasiswa - Penelitian, 2013)
This study is intended to take advantage of the chemical compounds contained in sponge species Petrosia alfiani as anti tuberculosis (TB). This study through the stages isolation, extraction, identification and bioactivity testing of chemical compounds Petrosia alfiani sponge. In this study produce chloroform extract as much as 20 g of solid resulting from 20 Kg wet sponge and also produce 4 pieces of pure compounds are not yet known its name.Keyword: Petrosia alfiani sponge, isolation, identication, bioactivity testing, chemical compounds.